THE PSYCHOLOGICAL IMPACTS OF SEXUAL ABUSE EXPERIENCED BY THE MAIN CHARACTER OF K.L RANDIS’ NOVEL SPILLED MILK - sri wahyuni; Riko Andika Rahmat Pohan; Parlindungan Purba (JURNAL ILMIAH BAHASA DAN SASTRA, 2019)
The title of this research is “The Psychological Impacts of Sexual Abuse Experienced by The Main Character of K.L Randis’ Novel Spilled Milk”. This study aims to determine the psychological impact of children on sexual abuse experienced by children. This research examines the phenomena of child abuse especially for sexual abuse and aim to reveal that literary work reflects social reality. The object of this research is “Spilled Milk” This novel shows that sexual abuse against children is a relationship between a child and an older person where the child is used as a satisfying object for the sexual needs of the offender. The method of this research that is used is Descriptive Qualitative. Data were obtained from words, phrases, clauses, or sentences in primary data. Data were analyzed by literary psychology approach and psychological theory. The psychological theories that are used in this thesis are the psychological impacts of sexual abuse by SECASA. The results of the psychological impact found in novel “Spilled Milk” are fear, responsibility, guilt and shame, anger and flashback or nightmare. So, hopefully this research is expected to be able to become a reference which can provide useful information child abuse and for people to prevent the act of child sexual abuse and help the victims.